Targeting type H vessels with bioactive metabolites from traditional Chinese botanical drugs: a therapeutic strategy for skeletal disorders - Tang, Shengping; Li, Jinkao; Dong, Zhuqing; Cai, Yangjie; Hu, Jianwei; Ding, Xiaofei; Liao, Shijie (Frontiers in Pharmacology, 2025)
Type H vessels are a specialized subtype of bone capillaries, first identified in 2014, characterized by high co-expression of CD31 and Endomucin. These vessels play a key regulatory role in bone development, repair, and remodeling through angiogenesis–osteogenesis coupling, which is essential for maintaining skeletal homeostasis. Type H vessels are abundant in the bones of young individuals but gradually decline with age, and their dysregulation is closely associated with skeletal disorders, including osteoporosis, osteoarthritis, bone defects, fractures, and osteonecrosis of the femoral head. Previous studies have identified the molecular mechanisms underlying the regulation of type H vessels, and recent investigations have examined pharmacological strategies to modulate these pathways. Among these, bioactive metabolites derived from traditional Chinese botanical drugs have attracted attention for their ability to regulate type H vessel formation and improve skeletal health. This review summarizes the molecular mechanisms by which these bioactive metabolites target type H vessels, highlighting their therapeutic potential in skeletal disorders and suggesting that modulation of type H vessel formation represents a promising strategy for intervention. Future studies are needed to further clarify the mechanisms of action of these metabolites and to assess their safety and clinical efficacy for translation into human therapy.